Mortalité estivale de l'huître creuse Crassostrea gigas dans le bassin de Marennes-Oléron - Couty, Angélique (2003)
The Japan oyster: Crassostrea gigas have been imported on the french coasts in the seventies and from this time it adapted to this environment. Since, it became the main oyster producted in France. But ,since twenty years C. gigas presents an anormaly and important mortality eah year in the period of summer. The syndrome known as summer mortality, appears particulary in mid-june. This mortality can affected 50% of the culture. Many studies have brought elements in the comprehension of the condition of apparition of this mortalilities. Temperature seems to play an important rule with reproductive maturation. But also, the deep ofwater could be associated to this mass mortality. The study began in march 2003 and characterize more precisely the summer mortality of the Pacific oyster C. Gigas in a variety of culture conditions. The thermal tolerance and the effect of maturation on mortalities have been confirmed. The proximity of the soil have been more precisely detailed, thanks to a new experienee of deplaeement of populations from a favorable (far from the soil) to a poor(near from the soi)l environment. This element takes a place in the magnitude of the losses. Moreover the study of growth during this period showed a physiologie stress. However, this year has been eharacterized by high temperatures but low degrees of mortalities, eomparatively to the last years. L'huître creuse du Japon: Crassostrea gigas, importée sur les côtes françaises dans les années 70 a su s'acclimater à notre environnement. Depuis, elle est devenue l'espèce principale cultivée par les professionnels. Pourtant depuis, le début des années 80, des épisodes récurrents de mortalité surviennent chaque année lors de la période printanière et estivale, avec des taux pouvant affecter plus de 50% du cheptel localement. Ce phénomène est depuis largement étudié par de nombreux organismes dont l'IFREMER et le laboratoire conchylicole du Poitou-Charente, qui depuis 1996, s’investit dans cette problématique. Ainsi, depuis sept ans , les mortalités ...